2001
DOI: 10.1007/s002840010176
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differentiation of Lactococcus lactis Subspecies lactis and cremoris Strains by Ribotyping and Site Specific-PCR

Abstract: Twenty-five strains of Lactococcus lactis subspecies lactis and subspecies cremoris obtained from dairy industry and environmental collections were examined by 16S RNA automated ribotyping profiles and site-specific PCR (S-PCR). By automated ribotyping, the majority of strains were classified in accordance with phenotypic characterization, with the exception of one lactis (220) and two cremoris (BO32 and 140) strains. A complete differentiation of subspecies lactis and cremoris in agreement with conventional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…cremoris and L lactis ssp. lactis biovar diacetylactis are used for the production of fermented dairy products and production of cheddar cheese 6. Therefore, exposure to unpasteurised dairy products has been suggested as a risk factor of L lactis cremoris infection.…”
Section: Discussionmentioning
confidence: 99%
“…cremoris and L lactis ssp. lactis biovar diacetylactis are used for the production of fermented dairy products and production of cheddar cheese 6. Therefore, exposure to unpasteurised dairy products has been suggested as a risk factor of L lactis cremoris infection.…”
Section: Discussionmentioning
confidence: 99%
“…The classification of L. lactis subspecies based on phenotypic characteristics is of primary importance in the dairy industry, as phenotypes directly reveal the abilities required in milk fermentation. It has been reported that PCR analysis with oligonucleotide primers designed for the rrnB-rrnC region correlates with phenotypic characterization (2).…”
mentioning
confidence: 99%
“…lactis biovar diacetylactis are used for the production of fermentated dairy products. L. lactis cremoris is particularly preferred for the production of chedar cheese (13). As a result, exposure to unpasteurized dairy products has been suggested as a risk factor of L. lactis cremoris infection.…”
Section: Discussionmentioning
confidence: 99%